The Role of Artificial Intelligence in Healthcare: A Critical Analysis of Its Implications for Patient Care - Mashabab, Mohammed Faisal; Sheniff, Mahdi Saleh Al; Alsharief, Mohammed Saleh; Yami, Mutared Ali Ali Al; Matnah, Hamad Naje Mana; Abbas, Abduallah Mohammed Al; Shenief, Hamad Yahya Mohsen Al; Abbas, Dhaffer Ali Ali Al Al; Raseen, Fahad Mana Saleh Abu; Kulayb, Ali Hamad Ali Al (Journal of Ecohumanism, 2024)
Artificial Intelligence (AI) is rapidly transforming healthcare, with significant implications for patient care. This article critically analyzes AI's role in improving healthcare delivery, focusing on diagnostic accuracy, personalized treatments, and system efficiency. It highlights key benefits such as enhanced decision-making, reduced human error, and the potential for better patient outcomes through AI-driven tools like predictive analytics and robotic surgery. However, the article also addresses challenges including ethical concerns, algorithmic bias, data privacy issues, and the need for clear regulations and accountability structures. The study explores how AI affects healthcare professionals, reshaping their roles and requiring new skill sets. Through case studies, the article illustrates both the successes and limitations of AI in clinical applications. Ultimately, this critical analysis emphasizes that while AI holds promise in improving patient care, responsible implementation is necessary to address ethical, legal, and technical challenges.